INSUFFISIENSI KATUP MITRAL PADA SEORANG PENDERITA LUPUS ERITEMATOSUS SISTEMIK - Sanjaya, Surya; Kambayana, Gede; Rina, I K; Raka Putra, Tjokorda (journal of internal medicine, 2008)
Systemic lupus erythematosus (SLE) is a multisystem inflammatory disease that is often difficult to diagnose and theetiology still unclear. Before the diagnosis can be established, four of eleven clinical and laboratory criteria must be met. Theprogression of SLE is acute fulminant, chronic remision and exacerbation. Prevalens of SLE in the many countries is variouslybetween 2.9 ? 400 per 100.000. SLE usually occur in reproduction period of human (15 ? 40 years old) and female is morecommon than male 5.5 ? 9.0 : 1. Cardiovascular manifestation of SLE is an serious case and increasing of mortality. Pericarditis,miocarditis and fibrinous Libmann-Sacks endocarditis are a common cardiovascular manifestation. Insufficiency of mitral andaorta valve is a rare complication of SLE and usually combination with pulmonal vein congestion and lung edema. We reporteda systemic lupus erythematosus with insufficiency mitral valve in Sanglah hospital because this case is very rare in populationand complicated. Accurate diagnosis of SLE is important because prompt treatment can reduce morbidity and mortality.